Interpretive Paradigm: Disclosure of Local Community Concern for the Environment (Study in Alas Purwo National Park Area, Banyuwangi, East Java) - Kartika Putri Kumalasari; Anisa Aprilia; Edlyn Khurotul Aini; Yusri Fajar; Anindya Prasasti (Department of Social Economy, Faculty of Agriculture , University of Brawijaya, 2023)
Alas Purwo National Park is a protected national park located in Banyuwangi, East Java, Indonesia. The Alas Purwo National Park currently allows for a variety of activities, including tourism and scientific study. In its development, the tourism industry must consider environmental, economic, social, and cultural factors, among others. Additionally, Alas Purwo National Park is a state-protected park, thus environmental sustainability must be considered. The aim of this research was to investigate how people interpret the notion of environmental stewardship. This researcher employed descriptive qualitative methods with primary data sources from informants who are Bedul and Alas Purwo Banyuwangi region residents engaged in economic activities. Determination of informants utilizing semi-structured interviews and open-ended questions based on snowball sampling. The results of the study indicate that the community in Alas Purwo National Park already appreciates the importance of caring for the environment and contributing to its preservation. Moreover, managers always maintain the ecosystem and advise visitors not to harm the native flora and wildlife.